Eksplorasi Pengalaman Anak Sekolah Dasar Dalam Menghadapi Stres Pembelajaran Akademik Pendidikan Islam Studi Kasus Siswa MI Baitul Huda Kelas VI - Susanti, Ely; Shanie, Arsan (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Academic stress is a common condition experienced by elementary school students, particularly within Islamic educational settings that demand both academic and religious achievements. This study aims to explore the experiences of sixth-grade students at MI Baitul Huda in dealing with academic pressure in Islamic Education learning. Using a qualitative case study approach, data were collected through in-depth interviews, direct observations, and document analysis involving selected students. The findings reveal that the main sources of stress stem from the heavy memorization workload, high academic performance expectations, and pressure from teachers and parents. To cope with stress, students adopt various strategies, such as seeking social support from peers and family, as well as engaging in religious coping through prayers and worship. The results highlight the importance of social support and spiritual approaches in helping madrasah students manage academic stress. This study provides a foundational reference for developing Islamic values-based interventions to support the psychological well-being of elementary students in madrasahs.